High Wind Speed Prevents the Establishment of the Disease Vector Mosquito Aedes albopictus in Its Climatic Niche in Europe - Adeleke, Emmanuel Damilare; Shittu, Ridwan Adeyemi; Beierkuhnlein, Carl; Thomas, Stephanie Margarete (Frontiers in Environmental Science, 2022)
Environmentally suitable habitats of Aedes albopictus (Ae. albopictus) in Europe are identified by several modelling studies. However, it is noticeable that even after decades of invasion process in Europe, the vector mosquito has not yet established in all its environmentally suitable areas. Natural barriers and human mediated transport play a role, but the potential of wind speed to explain Ae. albopictus’ absences, its inability to establish in its suitable areas is largely unknown. The current study therefore evaluates the potential of wind speed as an explanatory parameter of the non-occurrences of Ae. albopictus. We developed a global ecological niche model with relevant environmental parameters including wind speed and projected it to current climatic conditions in Europe. Differences in average wind speeds between areas of occurrences and non-occurrences of Ae. albopictus within its modelled suitable areas were tested for significance. A second global ecological niche model was trained with the same species records and environmental parameters however excluding wind speed parameters. Using multiple linear regression analyses and a test of average marginal effect, the effect of increasing wind speed on the average marginal effect of temperature and precipitation on the projected habitat suitability was estimated. We found that climatical suitable and monitored areas where Ae. albopictus is not established (3.12 ms-1 ± 0.04 SD) have significantly higher wind speeds than areas where the species is already established (2.54 ms-1 ± 0.04 SD). Among temperature-related bioclimatic variables, annual mean temperature was the most important variable contributing to the performance of both global models. Wind speed has a negative effect on predicted habitat suitability of Ae. albopictus and reduces false-positive rates in model predictions. With increasing wind speed, the average marginal effect of annual mean temperatures decreases but the one of annual precipitation increases. Wind speed should be considered in future modelling efforts aimed at limiting the spread and dispersal of Ae. albopictus as well as in the implementation of surveillance and early warning systems. Local-scale data collected from fieldwork or laboratory experiments will help to advance the state-of-the-art on how wind speeds influence the distribution, flight, and dispersal activity of the mosquito.